IT Professionals Versus the Public: Who’s More Optimistic About AI’s Future Impacts? - Ngo Thaiduong (SAGE Open, 2025)
Understanding the contrasting perspectives of Information Technology Professionals (ITPs) and the general public on artificial intelligence (AI) is crucial for responsible AI development and deployment, as these viewpoints can significantly influence its adoption and societal impact. This study investigates how ITPs’ deeper knowledge of Generative AI translates into differing viewpoints on its future impact, particularly on the job market. A quantitative content analysis of over 2,700 online newspaper comments in Vietnam reveals a more polarized perspective among ITPs. While both groups share job displacement concerns, ITPs express a wider range of beliefs, acknowledging both potential benefits and limitations of AI’s influence on the job market. Furthermore, ITP views remain relatively stable over time compared to the public’s increasing negativity toward AI. The analysis also highlights ITPs’ stronger focus on AI-driven efficiency gains alongside a more nuanced awareness of AI’s inherent shortcomings. This study contributes to the understanding of AI perception by highlighting the influence of technical expertise on shaping public opinion and offering insights for tailoring AI communication strategies.